2023
DOI: 10.3390/ijms24033025
|View full text |Cite
|
Sign up to set email alerts
|

Genomics, Proteomics, and Metabolomics Approaches to Improve Abiotic Stress Tolerance in Tomato Plant

Abstract: To explore changes in proteins and metabolites under stress circumstances, genomics, proteomics, and metabolomics methods are used. In-depth research over the previous ten years has gradually revealed the fundamental processes of plants’ responses to environmental stress. Abiotic stresses, which include temperature extremes, water scarcity, and metal toxicity brought on by human activity and urbanization, are a major cause for concern, since they can result in unsustainable warming trends and drastically lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 219 publications
(210 reference statements)
1
13
0
Order By: Relevance
“…Although prior to the presumptive annotation of the m/z_rt, the metabolome cannot be concluded to be more diverse when seedlings are grown under N-deprivation conditions, and based on the performed diversity analyses, we can conclude that independently of ESI mode, slightly more m/z_rt can be detected under the N-deprivation condition than under the control condition, suggesting that under N-deprivation conditions, the A. thaliana metabolome is more diverse in rosettes and roots, with rare increases in m/z_rt. The same occurs if the nia1 / nia2 double mutant (under either optimal or N-deprivation conditions) is compared with the WT grown under optimal N conditions, suggesting that when seedlings face stress conditions such as N-deprivation, their growth is arrested, with an increase in the diversity of m/z_rt (metabolites), prioritizing the synthesis (and the accumulation/abundance) of those that can be used to cope with stress, which is consistent with previous studies in which in plants, an increase in metabolomic complexity (prioritizing the availability of resources) was reported in order to cope with stress conditions and guarantee survival [ 14 , 92 ].…”
Section: Discussionsupporting
confidence: 89%
“…Although prior to the presumptive annotation of the m/z_rt, the metabolome cannot be concluded to be more diverse when seedlings are grown under N-deprivation conditions, and based on the performed diversity analyses, we can conclude that independently of ESI mode, slightly more m/z_rt can be detected under the N-deprivation condition than under the control condition, suggesting that under N-deprivation conditions, the A. thaliana metabolome is more diverse in rosettes and roots, with rare increases in m/z_rt. The same occurs if the nia1 / nia2 double mutant (under either optimal or N-deprivation conditions) is compared with the WT grown under optimal N conditions, suggesting that when seedlings face stress conditions such as N-deprivation, their growth is arrested, with an increase in the diversity of m/z_rt (metabolites), prioritizing the synthesis (and the accumulation/abundance) of those that can be used to cope with stress, which is consistent with previous studies in which in plants, an increase in metabolomic complexity (prioritizing the availability of resources) was reported in order to cope with stress conditions and guarantee survival [ 14 , 92 ].…”
Section: Discussionsupporting
confidence: 89%
“…It was believed to produce a variety of antioxidants, including flavonoids, phenols, lignin, and their precursors, to protect themselves from attack and prevent electrolyte leakage to surrounding tissues (Xu et al 2021). Flavonoids, a major secondary metabolite in plants, have various functions in plant development and in response to biotic and abiotic stress (Nakabayashi et al 2014;Saito et al 2013). In our study, especially in T1 treatment, the flavonoid biosynthesis was significantly enhanced in restriction treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fruit quality mainly includes primary and secondary metabolites (Wahid and Ghazanfar 2006). It was reported that plant metabolites increase under abiotic stress (Naik et al 2023). Root restriction is a kind of physical stress.…”
mentioning
confidence: 99%
“…Solanum lycopersicum plants, when exposed to drought stress, decrease the leaf area and photosynthetic level. This final result in a reduction in the accumulation of biomass and yield [ 9 ]. Pappula-Reddy et al [ 10 ] found that water stress can result in yield reductions ranging from 13 to 94%, contingent upon the duration and intensity of the drought stress.…”
Section: Introductionmentioning
confidence: 99%